The preparation and morphology of biphasic calcium phosphate ceramics - Saiwanich P. (2014)
In this work, thepreparation and morphology of biphasic calcium phosphate (BCP) have been studied. The biphasic calcium phosphate(BCP) ceramics were prepared by mixing between hydroxyapatite (HA) and Beta-tricalcium phosphate (β-TCP) powder by ball milling technique with different ratios (100:0, 80:20, 60:40, 50:50, 40:60, 20:80 and 0:100). After that the mixtures were forming by Gel casting method and then sintered at 1200°C, respectively. The phase formation of the biphasic calcium phosphateceramics were studied by X-ray diffraction (XRD) and their ceramic microstructure, shrinkage and density were investigated. © (2012) Trans Tech Publications.